Hiding Data in Color Image Using Least Significant Bits of Blue Sector - L. Hussein, Hussein (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Concealing the existence of secret hidden message inside a cover object is known as steganography, which is a powerful technique. We can provide a secret communication between sender and receiver using Steganography. In this paper, the main goal is for hiding secret message into the pixels using Least Significant Bit (LSB) of blue sector of the cover image. Therefore, the objective is by mapping technique presenting a model for hiding text in an image. In the model for proposing the secret message, convert text to binary also the covering (image) is divided into its three original colors, Red, Green and Blue (RGB) , use the Blue sector convert it to binary, hide two bits from the message in two bits of the least significant bits of blue sector of the image.